An Account on the Versatility of Dopamine as a Functional Monomer in Molecular Imprinting. Issue 17 (2nd May 2019) - Zaidi, Shabi Abbas
Abstract: Apart from being a vital catecholamine molecule responsible for the proper functioning of central nervous system (CNS), hormonal and renal systems, dopamine (DA) has also been increasingly employed as a functional monomer in the fabrication of surface molecular imprinting of valuable analytes, especially for proteins. The application of dopamine as functional monomer was inspired from mussel adhesion protein, its capability of self‐polymerization under weak alkaline aqueous solution resulting into thin biocompatible highly cross‐linked polydopmaine (PDA) film and cost‐effectiveness. Furthermore, it could adhere strongly on various (organic and inorganic) substrates without any attachment, and possesses plenty of noncovalent functionalities such as amino‐containing groups, hydroxyl‐containing groups and π‐π for further modifications. In this first ever review, we focused our attention on the utilization and influence of DA as a functional monomer in the fabrication of molecular imprinting and discussed it comprehensively. Abstract : This works describes the utilization and capability of Dopamine (DA) as a functional monomer for molecular imprinting inspired from mussel adhesion protein. DA can be self‐polymerized under weak alkaline aqueous solution resulting into thin biocompatible highly cross‐linked polydopmaine (PDA) film. We discussed various works which have explored the unique feature of DA for the fabrication of diverse types of imprinted polymers. The current challenges, remedies, and, the future direction of MIPs in this area are highlighted.